2017
DOI: 10.14740/jocmr3029w
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association Between Toxoplasma gondii Infection and Diabetes Mellitus: A Matched Case-Control Study in a Mexican Population

Abstract: BackgroundVery little is known about the association between infection with Toxoplasma gondii (T. gondii) and diabetes mellitus. We perform an age- and gender-matched case-control study to determine the association of T. gondii infection and diabetes mellitus.MethodsCases included 156 patients with diabetes mellitus and 156 controls without diabetes mellitus who attended in two public clinics in Durango City, Mexico. Sera of cases and controls were tested for the presence of anti-Toxoplasma IgG and IgM antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
(30 reference statements)
3
11
1
Order By: Relevance
“…The seroprevalence of T. gondii is therefore higher in subjects with T2DM than health controls. Hence, all except three studies (Khalili et al 2018;Alvarado-Esquivela et al 2017;Siyadatpanah et al 2013) reported a significant relationship between T. gondii infection and T2DM (p < 0.05). The pooled ORs of all included studies ranged from 1.08 (95% CI 0.69-1.70) to 4.52 (95% CI 3.26-6.28) with six of these results being significant (p < 0.05).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…The seroprevalence of T. gondii is therefore higher in subjects with T2DM than health controls. Hence, all except three studies (Khalili et al 2018;Alvarado-Esquivela et al 2017;Siyadatpanah et al 2013) reported a significant relationship between T. gondii infection and T2DM (p < 0.05). The pooled ORs of all included studies ranged from 1.08 (95% CI 0.69-1.70) to 4.52 (95% CI 3.26-6.28) with six of these results being significant (p < 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…The remaining 25 papers were read as abstracts with 12 being rejected due to being literature reviews or animal studies. The residual 13 papers (Li et al 2018;Khalili et al 2018;Han et al 2018;Molan and Ismail 2017;Alvarado-Esquivela et al 2017;Saheb 2017;Nihad and Hamad 2017;Hemida et al 2017;Saki and Shafieenia 2016;Modrek et al 2015a;Siyadatpanah et al 2013;Shirbazou et al 2013;Gokce et al 2008), as summarised in Table 1, were read in full and three studies (Han et al 2018;Hemida et al 2017;Modrek et al 2015a) were excluded as they lacked a control group and hence did not meet the inclusion criteria. The references of the review articles did not add any new studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations